2014
DOI: 10.1111/ppl.12144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mineral supplies in Africa

Abstract: Dietary micronutrient deficiencies (MNDs) are widespread, yet their prevalence can be difficult to assess. Here, we estimate MND risks due to inadequate intakes for seven minerals in Africa using food supply and composition data, and consider the potential of food-based and agricultural interventions. Food Balance Sheets (FBSs) for 46 countries were integrated with food composition data to estimate per capita supply of calcium (Ca), copper (Cu), iron (Fe), iodine (I), magnesium (Mg), selenium (Se) and zinc (Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(234 citation statements)
references
References 98 publications
14
215
4
1
Order By: Relevance
“…For example, the 2011 Pakistan National Nutrition Survey Report (NNS 2011) reported that 42 % (n = 5953) and 48 % (n = 791) of non-pregnant and pregnant women respectively and 37 % (n = 2499) of children <5 years were Zn-deficient, based on having plasma Zn concentrations <60 μg Zn dL −1 . This discrepancy is likely to be due to: (1) an over-estimate of dietary Zn supply, considering the use of USDA food composition data for food items other than wheat and considering that food supply data does not account for household-level wastage; (2) the assumption of a 25 % coefficient of variation in dietary Zn intakes may underestimate the inequality of access to food due to socio-economic or social exclusion factors (Joy et al 2014Kumssa et al 2015a, b;Kuper et al 2015); and (3) nutritional Zn deficiency can occur despite adequate dietary Zn supply due to factors such as diarrhoeal disease.…”
Section: Methodsmentioning
confidence: 98%
“…For example, the 2011 Pakistan National Nutrition Survey Report (NNS 2011) reported that 42 % (n = 5953) and 48 % (n = 791) of non-pregnant and pregnant women respectively and 37 % (n = 2499) of children <5 years were Zn-deficient, based on having plasma Zn concentrations <60 μg Zn dL −1 . This discrepancy is likely to be due to: (1) an over-estimate of dietary Zn supply, considering the use of USDA food composition data for food items other than wheat and considering that food supply data does not account for household-level wastage; (2) the assumption of a 25 % coefficient of variation in dietary Zn intakes may underestimate the inequality of access to food due to socio-economic or social exclusion factors (Joy et al 2014Kumssa et al 2015a, b;Kuper et al 2015); and (3) nutritional Zn deficiency can occur despite adequate dietary Zn supply due to factors such as diarrhoeal disease.…”
Section: Methodsmentioning
confidence: 98%
“…There are potential weaknesses i n u s i n g F B S f o o d s u p p l y d a t a i n c l u d i n g underestimating food supply as some subsistence production is not captured, or overestimating supply by failing to account for household-level food waste (FAO 2001). These weaknesses have been discussed extensively elsewhere (de Haen et al 2011;Joy et al 2014). A further source of error may arise from composition data derived from sources that will not capture local variation in elemental composition of crops and there is a lack of spatially-resolved food composition data in sub-Saharan Africa (Joy et al 2014;Joy et al 2015).…”
Section: Baseline Dietary Zn Supplies and Deficiency Prevalencementioning
confidence: 99%
“…Other agricultural strategies to increase the concentration of Zn in harvested grain include crop breeding for high-Zn varieties (Cakmak 2008;Broadley 2009, 2011;Bouis and Welch 2010), while soaking or 'priming' of seeds in ZnSO 4 solution might be more efficient than soil applications and confer yield benefits (Slaton et al 2001;Harris et al 2007;Harris et al 2008) although increased Zn concentration in progeny grain is not consistently reported (Johnson et al 2005). It may also be possible to breed lower PA concentrations into the grains of staple crops and the benefits of even marginal reductions in grain PA concentration on Zn bioavailability could be large at population scales (Joy et al 2014). Interestingly, it has been reported that Zn-enriched fertilisers can decrease concentrations of PA in cereal grains while Zn deficiency may lead to increased P uptake and accumulation in plants (Loneragan et al 1982;Erdal et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in more detail in a subsequent section, such negative outcome in the overall micronutrient levels of plants upon the addition of a specific micronutrient could be due to competition for uptake that occurs among micronutrients, which becomes heightened with an imbalance in the soil proportions of the applied versus nonapplied but competing nutrients. Therefore, agronomic fortification with micronutrients should be an intervention in situations where specific micronutrients have been determined to be limiting for crop productivity, as well as for the health and well-being of animals and humans whose primary source of food includes such crops (Joy et al 2014;Kumssa et al 2015). However, achieving this would require prior crop-and soil-specific evaluations, to elucidate to what extent the micronutrient to be intervened in affects the nutritional levels of other micronutrients, by systematically determining nutrient ratios and antagonistic uptake interactions among the micronutrients, and between micronutrients and macronutrients.…”
Section: Role Of Micronutrients In Crop Nutritional Qualitymentioning
confidence: 99%